Young, Empowered & strong (YES): a study protocol paper for a randomized controlled trial of an mHealth symptom monitoring and self-management intervention for adolescent and young adult (AYA) breast cancer survivors - Kate E Dibble; Shoshana M Rosenberg; Craig Snow; Gregory J Kirkner; Nabihah Tayob; Magnolia Contreras; Noel D Roma; Cecilia R DeGraffinreid; Timiya S Nolan; Dawn L Hershman; Michelle Naughton; Ann H Partridge (BMC Public Health)
Abstract Background Compared to older adults with breast cancer (BC), adolescents and young adults (AYAs) develop more aggressive disease necessitating more intensive therapy with curative intent, which is disruptive to planned life trajectories. The burden of unmet needs among AYA BC survivors exists in two domains: (1) symptoms (e.g., sexual problems, anxiety, fatigue, stress, hot flashes) and (2) AYA concerns (e.g., fertility, genetics, relationships, economic attainment). Improved attention to concerns and symptoms may improve symptom management and quality of life. The Young, Empowered and Strong (YES) trial tests the efficacy of a 9-month, multicomponent digital health intervention that includes monthly assessments of prevalent symptoms, a chat room, and journal to engage and support AYAs with BC by providing tailored information, resources, and support outside of the clinical setting. Methods YES is a multicenter, randomized controlled trial across three academic institutions in the United States with 400 participants randomized to either the YES intervention or usual care arm. Inclusion criteria include biologically female; 15–39 years of age at diagnosis of stage 0-III BC; within 3 years of diagnosis; no known evidence of recurrence; no prior history of new malignancy since initial BC diagnosis; and ability to access medical records from treatment site. All participants complete REDCap surveys at baseline, and at 3, 6, and 9 months post-enrollment. The primary outcome is quality of life as measured by the Quality of Life in Adult Cancer Survivors Scale (QLACS), with changes from baseline to 6-months in QLACS scores, compared by arm. Secondary outcomes include patient reported AYA concerns/needs, emotional symptoms, general health, physical symptoms, and health behaviors, Discussion Study findings will provide valuable insight into the ability of the YES digital health intervention to address symptoms and concerns of AYA BC survivors and assist them to track and self-manage their own symptoms, concerns, and needs related to their cancer outside of the clinic. Trial registration Clinicaltrials.gov, NCT04906200, registered May 13, 2021.